Nutritional Status of Adolescent School Girls of Uttarakhand. (3rd October 2017) - Dutta, A.; Shukla, P.; Tiwari, N.; Singhal, P.; Khan, R.
ABSTRACT: India has the highest number of adolescents in the world (20.9%). Nutritional intake of girls is on the decline with serious health implications. The study was conducted in two districts of Uttarakhand to determine the prevalence of malnutrition among adolescent girls in the context of socioeconomic factors. The objective was to assess the nutritional status, deficiency symptoms, and socioeconomic background of girls aged 12-15 years (n=300). The results revealed that three percent of the subjects were severely undernourished, 11.67 percent were moderately undernourished, twenty-one percent were stunted and 21.33 percent were thin. No significant association was found between BMI and variables such as age, family type, family income, food habits and meal pattern. Significant clinical symptoms were pale conjunctiva (24.33%), mottled teeth (23.33%), cavities in teeth (21.33%) and spongy bleeding gums (18.67%). Mean energy intake and several micronutrients were lower than recommended values.